2017
DOI: 10.1039/c6fo01468b
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and supramolecular structural changes of maize starch by non-covalent interactions with gallic acid

Abstract: The effects of non-covalent interactions between gallic acid (GA) and starch on starch digestibility and supramolecular structural changes (short-range ordered molecular structure, crystalline structure, lamellar structure and fractal structure) were investigated. The results indicated that the digestibility of both starches was substantially reduced in the rapidly digestible starch (RDS) content, but resistant starch (RS) was increased after interacting with GA. The RS content of starch-GA complexes ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(66 citation statements)
references
References 51 publications
2
64
0
Order By: Relevance
“…0.65 nm −1 was disappeared for all the starch samples due to the complete disruption of multi-scale structures of starch granules after hydrothermal treatment. According to the literature, the SAXS intensity at low-q region was correlated with the difference in the electron density between ordered and amorphous regions (Chi et al, 2017;Suzuki, Chiba, & Yano, 1997). It can be seen that the intensity of RSG-1 and RSG-2 at low-q region was higher than that of RSG, indicating RSG-1 and RSG-2 had a larger difference in the electron density between ordered and amorphous regions.…”
Section: Aggregation Structures Of Starch-ga Complex Gelsmentioning
confidence: 90%
See 1 more Smart Citation
“…0.65 nm −1 was disappeared for all the starch samples due to the complete disruption of multi-scale structures of starch granules after hydrothermal treatment. According to the literature, the SAXS intensity at low-q region was correlated with the difference in the electron density between ordered and amorphous regions (Chi et al, 2017;Suzuki, Chiba, & Yano, 1997). It can be seen that the intensity of RSG-1 and RSG-2 at low-q region was higher than that of RSG, indicating RSG-1 and RSG-2 had a larger difference in the electron density between ordered and amorphous regions.…”
Section: Aggregation Structures Of Starch-ga Complex Gelsmentioning
confidence: 90%
“…Nevertheless, there is insufficient knowledge on whether and how dietary phenolics such as GA can vary the hydrogen-bonding network and the ordering of starch. In our previous research, we found that GA could alter the starch semi-crystalline structure by interacting with starch in a non-covalent way, which decreases the starch digestibility (Chi et al, 2017). However, phenolic compounds have been reported with the potential of inhibiting starch retrogradation rather assisting starch reassembly (Wang, Li, Copeland, Niu, & Wang, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, ASS had the highest degree of crystallization which follows the orders of ASS > MS > PS. According to previous studies (Chi et al, 2017;Lopez-Rubio, Flanagan, Shrestha, Gidley, & Gilbert, 2008),…”
Section: Crystal Propertiesof Starchesmentioning
confidence: 99%
“…In order to further clarify the structural parameters of semi-crystalline lamellae, one-dimensional correlation function profiles were calculated according to following equation (Chi et al, 2017;Kuang et al, 2017)…”
Section: Lamellar Structurementioning
confidence: 99%
See 1 more Smart Citation